Analysis and risk assessment of risk technical systems to develop of methodology for teaching students using the method dynamic fault tree - Simeonova, Tsvetelina (Yearbook Telecommunications, 2019)
The aim of the present work is to develop a methodology for conducting exercises for analysis, assessment and management of risk, using a web based tool, by identifying and analyzing the risk of occurrence of a dangerous event through the dynamic fault tree method. As a result, a framework is presented according to the proposed methodology applicable to the students’ training in risk analysis, evaluation and management, and according to accepted assumptions. Approaches for qualitative and quantitative risk assessment are presented at the assumed value of the damages. In addition, a methodology for risk analysis, assessment and management applicable to student training on risk analysis and management, through the dynamic fault tree method, has been developed and proposed.